Word deafness with preserved number word perception. Issue 8 (17th November 2018) - Fischer-Baum, Simon; Mis, Rachel; Dial, Heather
ABSTRACT: We describe the performance of an aphasic individual, K.A., who showed a selective impairment affecting his ability to perceive spoken language, while largely sparing his ability to perceive written language and to produce spoken language. His spoken perception impairment left him unable to distinguish words or nonwords that differed on a single phoneme and he was no better than chance at auditory lexical decision or single spoken word and single picture matching with phonological foils. Strikingly, despite this profound impairment, K.A. showed a selective sparing in his ability to perceive number words, which he was able to repeat and comprehend largely without error. This case adds to a growing literature demonstrating modality-specific dissociations between number word and non-number word processing. Because of the locus of K.A.'s speech perception deficit for non-number words, we argue that this distinction between number word and non-number word processing arises at a sublexical level of representations in speech perception, in a parallel fashion to what has previously been argued for in the organization of the sublexical level of representation for speech production.